The NCATS Pharmaceutical Collection: a 10-year update. Issue 12 (December 2019) - Huang, Ruili; Zhu, Hu; Shinn, Paul; Ngan, Deborah; Ye, Lin; Thakur, Ashish; Grewal, Gurmit; Zhao, Tongan; Southall, Noel; Hall, Mathew D.; Simeonov, Anton; Austin, Christopher P.
Highlights: ⿢ NPC repurposing screens discovered compounds with new clinical indications. ⿢ Systematic NPC screening data establishes rich drug activity signatures. ⿢ NPC data in the public domain provides a resource for drug discovery community. ⿢ NPC is brought up-to-date with small molecule drugs approved in recent years. Abstract : The National Center for Advancing Translational Sciences (NCATS) Pharmaceutical Collection (NPC), a comprehensive collection of clinically approved drugs, was made a public resource in 2011. Over the past decade, the NPC has been systematically profiled for activity across an array of pathways and disease models, generating an unparalleled amount of data. These data have not only enabled the identification of new repurposing candidates with several in clinical trials, but also uncovered new biological insights into drug targets and disease mechanisms. This retrospective provides an update on the NPC in terms of both successes and lessons learned. We also report our efforts in bringing the NPC up-to-date with drugs approved in recent years.